SANTRI RECEPTION AGAINST SAMADIYAH RECITATION TO FREE THE CORPSE FROM THE TORMENT OF THE GRAVE - Romziana, Luthviyah; Fatimah, Fatimah; Putri, Amelia; Fajarwati, Linda (Universitas Nurul Jadid, 2022)
Today, the Qur’an is not only studied textually but has begun to be examined in the dialectical realm, which is familiar with the term living Qur’an. This can be highlighted through the reading of Samadiyah (100,000 Sūrah Al-Ikhlāṣ), which has become a tradition in the archipelago, including the students of the Al-Lathifiyah area of the Pondok Pesantren Nurul Jadid in Paiton Probolinggo. This study aims to analyze the reception of students in the Al-Lathifiyah region towards the reading of Samadiyah addressed to people who have died. These activities are carried out within a certain period using calculating tools such as prayer beads, coffee, corn, etc. The reading of the Samadiyah is believed to be an intermediary for releasing the corpse from the torment of the grave. The meaning of reading Samadiyah implies a desire to be able to atone for the sins of people who have died. In this study, we used qualitative research with a phenomenological approach. The data collection techniques we use are observation, interviews, and documentation. From the reception of the students of the Al-Lathifiyah region towards the tradition of reciting Samadiyah for the dead, it can be concluded that the reading of Samadiyah can send blessings to those who have died so that they can atone for the torment of the grave and their sins.